2022
DOI: 10.2460/javma.22.08.0341
|View full text |Cite
|
Sign up to set email alerts
|

Body condition and hair coat length impact weight estimation in dogs and cats presented to an emergency department

Abstract: OBJECTIVE To examine weight estimations by veterinarians, veterinary nurses, and veterinary students to determine the accuracy of weight estimation in a veterinary emergency department. Secondary objectives included an initial evaluation of how body condition score (BCS), hair coat length, and hospital position of the estimator impacted accuracy of weight estimation. ANIMALS 101 dogs and 28 cats that presented to the emergency department from October 17, 2017, to September 3, 2019. PROCEDURES A written for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The lack of statistical significance found in this study aligns with previous human and veterinary studies, which suggest that the accuracy of weight estimation tends to be compromised by underweight children and small dogs, respectively. 9,11,16 A previous study by Wolf and Drobatz 12 demonstrated that a higher BCS induced overestimation of cats’ weight by veterinary staff. The cats’ BCS was not evaluated in this study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The lack of statistical significance found in this study aligns with previous human and veterinary studies, which suggest that the accuracy of weight estimation tends to be compromised by underweight children and small dogs, respectively. 9,11,16 A previous study by Wolf and Drobatz 12 demonstrated that a higher BCS induced overestimation of cats’ weight by veterinary staff. The cats’ BCS was not evaluated in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Approximately 20% (6/28) of weight estimations in cats were within 10% of the cat's actual body weight. 12 Unlike dogs, cats tend to have a narrower range of body weights, which may make weight estimation easier. The impact of estimating a higher or lower body weight in making treatment decisions is likely also less significant in cats due to their average smaller body weight compared with dogs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation